(untitled) (Journal of Science and Technology, 2016)
Effects of in-vitro propagation and forcing on the quality of pineapple juice from pineapple fruit (Ananas comosis LI) using the cultivator “sugar loaf” were investigated. Juice quality indices measured for in vitro propagated forced fruits were pH 3 6 - 4 3 brix-acid ratio 16 2 – 30 7 reducing sugars 0 5 – 2 1. Values for naturally propagated and forced fruits were pH 3 5 – 4 5 brix-acid ratio 19 5 – 26 7, reducing sugars 1 5 to 2 5. There were no significant differences (p >0.05) between the two sets of quality indices. Similar results were observed when the quality indices for juice from in vitro propagated and naturally flowered fruits were compared with those from naturally propagated and naturally flowered fruits. The results suggest that in vitro propagation and forced flowering may be used in the production of pineapple fruits without any significant difference on fruit juice quality. Forced flowering also had no significant effect (p> 0.05) on the quality of fruit juice from naturally propagated “Smooth cayenne” another cultivator of (Ananas comosis LI).